2016
DOI: 10.1111/ijlh.12559
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of bone marrow morphologic findings in hepatitis C patients with and without prior liver transplantation

Abstract: Cytopenia is a common finding in hepatitis C patients. Hypersplenism or LT has an adverse impact on some blood cell counts. Lastly, hepatitis C patients present with a wide spectrum of BM findings including malignant neoplasms, which indicates a diagnostic value of BM examination in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The prevalence of bone marrow abnormalities that may be the underlying pathology is largely understudied. Several authors had studied the bone marrow findings in patients with hepatitis C 10–12. Anwar et al 13 studied the utility of bone marrow examination in patients with CLD and found this test to be quite useful especially in patients with severe pancytopaenia and those with sudden alterations in peripheral cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of bone marrow abnormalities that may be the underlying pathology is largely understudied. Several authors had studied the bone marrow findings in patients with hepatitis C 10–12. Anwar et al 13 studied the utility of bone marrow examination in patients with CLD and found this test to be quite useful especially in patients with severe pancytopaenia and those with sudden alterations in peripheral cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Das et al reported a 10-year-old girl infected with HAV that developed pancytopenia (3). In addition to HAV, hepatitis due to other viruses, including hepatitis G (HGV) and HCV has also been described along with pancytopenia (9,10). Despite that this is unusual, it is advisable to consider bone marrow failure in the patients infected with hepatitis and present with a decreased count of all blood cell lineages.…”
Section: Discussionmentioning
confidence: 99%